Thermal analysis of chicken fiber augmented epoxy composites. (2021) - Sah, Neha; Goel, Alka; Chaudhary, Arun Kumar; Verma, Alka
Abstract: The structural properties of chicken feathers, a poultry by-product, promote its better utilization over dumping or incineration and polymer composites present one such area where they can be used directly without much processing. In this research, epoxy composites augmented with chicken feather fibers in open fibrous and nonwoven mat forms were prepared and tested for their thermal stability. Thermogravimetry (TG) and differential thermal analysis (DTA) characterization were done using the heating rate of 100 °C/min from 0 to 700 °C. The results show three stages of thermal decomposition including evaporation of moisture below 150 °C, breakdown of chicken fibers within the range of 250 to 350 °C, and final degradation of the matrix at above 450 °C. Insignificant difference was observed in thermal stability with an increase in chicken fiber content and also with mat as reinforcement forms.